Analisis Employer Attractiveness pada PT Goto Gojek Tokopedia Tbk : (Survei pada Mahasiswa dan Alumni Angkatan 2019 Jurusan IT dari Universitas Padjadjaran, ITB, dan Universitas Telkom) - Annisa, Friska Rahmah; Rivani (Universitas Sam Ratulangi, 2024)
This research aims to determine the condition of employer attractiveness at PT GoTo Gojek Tokopedia Tbk and analyze the most dominant factors shaping employer attractiveness. The method used in this research is the quantitative method through a survey. The population in this research is undergraduate students and alumni of IT in 2019 from Universitas Padjadjaran, Institut Teknologi Bandung, Universitas Telkom with a sample of 87 people. The sampling technique used is non-probability sampling with a purposive sampling technique. The data analysis technique was used with the Employer Attractiveness Scale (EmpAt Scale) measuring instrument and the Second Order Confirmatory Factor Analysis method using linear structure model (LISREL) version 8.5. The results of the analysis show that the employer attractiveness of PT GoTo Gojek Tokopedia Tbk is in the category of fairly good based on eleven dimensions and career growth value, familiarity value, and role value are among the top three factors considered in choosing PT GoTo Gojek Tokopedia Tbk as a company to work.